Ethical Education and Student Academic Misconduct (A Comparative Study on Undergraduate Students of Accounting and Management Departments) - Maulana, Alysha Sal'wa; Djamhuri, Ali (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
This research aims to conduct a comparative test to determine whether academic misconduct in the accounting department is less prevalent than in the management department due to different ethical quantity exposures. In this case, students in both departments must meet the criteria: they must have passed the Business Ethics subject and, for accounting students, the additional subject Auditing 1 (Assurance and Attestation). This research employs a quantitative method, using a questionnaire as the research instrument, involving a sample of 295 undergraduate students from the Accounting and Management Departments, Faculty of Economics and Business, Universitas Brawijaya, classes of 2017 to 2020. The results of the hypothesis testing utilising the Mann-Whitney U test indicate no significant difference in the prevalence of academic misconduct between the two departments.